(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
This study explores the baris dadap dance as a sacred art form of the Bali Aga community in Cempaga Village, Banjar District, Buleleng Regency. The dance functions not only as an artistic expression but also as a religious, social, and cultural medium embedded within the community’s spiritual and customary systems. Using a qualitative approach, this research analyzes three main aspects: the mythological and religious foundations of the dance, its social and structural functions, and its impact on the local economy and religious tourism. Findings show that the baris dadap dance plays a vital role in maintaining harmony among humans, nature, and ancestral spirits, while also strengthening community solidarity through the transmission of values and ritual practices. Moreover, the dance contributes to local economic growth through active participation in community-based cultural and spiritual tourism. These findings affirm that the baris dadap dance serves as an adaptive and relevant means of cultural preservation, symbolizing the cultural resilience of the Bali Aga identity amid changing times.